A study to determine risk factors for renal scarring as detected by dimercaptosuccinic acid scan in children with urinary tract infection - Jacob, Nisha Jacob Arackal; Koripadu, Seshagiri; Yanamandala, Harishchandra Venkata (International Journal of Contemporary Pediatrics, 2021)
Background: The aim of the study was to determine the risk factors for renal scarring detected by DMSA (dimercaptosuccinic acid) scan in children with culture-proven urinary tract infection (UTI). Methods: A hospital based observational case-control study was conducted from 2018 June to 2020 June in children aged between 1 month to 5 years who underwent a DMSA scan following culture-proven UTI (N=72). Of the children fulfilling the criteria, 43 had renal scarring in the DMSA scan as a case group and the remaining 29 children who had no renal scarring were taken as a control group. Results: Of the total 72 cases with culture-positive UTI, 59% of patients had renal scarring and the rest and 40% were scar negative. There was no significant difference in the renal scarring observed with respect to age in the two groups. There was significant (p<0.05) the association noted between renal scarring and VUR (vesicoureteric reflux). A significant difference was observed in the renal scarring between the two groups regarding the presence of recurrent UTI (p=0.000). Although most cases (97.7%) had a fever in the DMSA positive group, this was not a significant risk factor for scarring (p>0.05). In DMSA positive group, circumcision was not a significant risk factor for scarring. Conclusions: VUR and recurrent UTI were significant risk factors for renal scarring in children with culture-proven UTI as detected by DMSA scan. The other risk factors like age, sex, fever, leucocytosis and circumcision were not found to be significant.